A corpus-cognitive approach to ideological attention in discourse - Kreischer, Kim-Sue (2019)
This thesis develops a corpus-cognitive approach to discourse analysis centred on the patterns of attention created in texts, addressing the challenge of providing a cognitively valid analysis of discourse. It uses traditional methods from corpus linguistics and the notion of construal from cognitive grammar, with the concept of mind-modelling as central for analysing ideological viewpoints. I describe how attentional patterns construct ideology in newspaper texts on the debate on abortion access in the Republic of Ireland and Northern Ireland with case studies of Direct Speech, double quotations, and co-occurring discourses. The results overall provide a valuable new perspective on how textual patterns con- struct points of attention and proffer ideological readings to the audience. I develop and analytically test the attentional framework, which gives guidance on how attention is directed by drawing on cognitive and corpus linguistic principles. Detailed analysis of one text demonstrates how to account for personal, voluntary attention and readings, which is a major concern for discourse analysis. Analyses of direct speech in the corpus reveal that it has uses indicative of the debate, with the cognitive analysis of the semantic domain of happiness highlighting its use as a means of voicing an ideological perspective while seemingly remaining objective. I further explore how writers communicate the intended viewpoint of their texts when several perspectives are presented in double quotations. I suggest writers reduce the perspectives offered to maintain their relation with the readers and provide a categorisation of this relation. Lastly I analyse the relation and function of co-occurring discourses for creating ideology during the debate of the death of Savita Halappanavar. Results indicate that the discourses voiced about certain concepts changes in the presence of other concepts. Specifically, the discourses about a mother differ when the concept of the church is present in a text. The cognitive analyses detail how an ideology is then created by putting certain discourses into the attentional foreground or background. The findings demonstrate that when statistical and qualitative evidence augment each other, then the complexity of first, creating an ideological viewpoint in a text and second, for the reader to understand it can be more accurately described.